Gambaran Perkembangan Kognitif Pada Anak Autisme: Description of Cognitive Development in Autistic Children - Aka Watrina Anindita; Aratsa Nurhayati; Rizky Raudhatul Jannah; Naeila Rifatil Muna (Universitas Ngudi Waluyo, 2024)
Children's cognitive development is a thinking process that allows their brains to recognize, know, understand and reason so that they can understand material more easily. However, for children with special needs, there are certainly slight differences in cognitive development from children in general. Autism is a condition where individuals are more interested in their own world and tend not to want to interact socially with the people around them. This study aims to collect information about the cognitive development of 6 year old autistic children. This research uses a qualitative descriptive approach with a sample of one autistic child who attends Kindergarten